NovaSil clay intervention in Ghanaians at high risk for aflatoxicosis: II. Reduction in biomarkers of aflatoxin exposure in blood and urine - Wang, P.; Afriyie-Gyawu, E.; Tang, Y.; Johnson, N.M.; Xu, L.; Tang, L.; Huebner, H.J.; Ankrah, N.A.; Ofori-adjei, D.et.al (Food Additives and Contaminants - Part A Chemistry, Analysis, Control, Exposure and Risk Assessment, 2008)
The efficacy of NovaSil clay (NS) to reduce aflatoxin (AF) biomarkers of exposure was evaluated in 656 blood samples and 624 urine samples collected from study participants during a 3-month phase IIa clinical intervention trial in Ghana. NS was delivered before meals via capsules. Serum AFB1–albumin adduct was measured by radioimmunoassay and urinary AFM1 metabolites were quantified by immunoaffinity-high-performance liquid chromatography (HPLC)-fluorescence methods. Levels of AFB1–albumin adduct in serum samples collected at baseline and at 1 month were similar (p = 0.2354 and p = 0.3645, respectively) among the placebo (PL), low dose (LD, 1.5 g NS day−1), and high dose (HD, 3.0 g NS day−1) groups. However, the levels of AFB1–albumin adduct at 3 months were significantly decreased in both the LD group (p < 0.0001) and the HD group (p < 0.0001) compared with levels in the PL group. Levels of AFM1 in urine samples collected at baseline and at 1 month were not statistically different among the three study groups. However, a significant decrease (up to 58%) in the median level of AFM1 in samples collected at 3 months was found in the HD group when compared with the median level in the PL group (p < 0.0391). In addition, significant effects were found for dose, time, and dose–time interaction with serum AFB1–albumin adduct and dose–time interaction with urinary AFM1 metabolites. The results suggest that capsules containing NS clay can be used to reduce effectively the bioavailability of dietary AF based on a reduction of AF-specific biomarkers. © 2008 Taylor & Francis Group, LLC.
Keywords: Aflatoxicosis; Biomarkers; Fungal metabolites; NovaSil clay